2005
DOI: 10.1037/0002-9432.75.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Mental Illness: Tests of the Social Causation and Selection Hypotheses.

Abstract: This study tests several hypotheses about the underlying causal structure of the inverse correlation between socioeconomic status (SES) and mental illness. It does this through the analysis of a longitudinal statewide database on acute psychiatric hospitalization in Massachusetts for the fiscal years 1994–2000 as well as supplemental census data. The modeling strategy used techniques of structural equation modeling and found that SES impacted directly on rates of mental illness as well as indirectly through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
367
6
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(437 citation statements)
references
References 24 publications
43
367
6
7
Order By: Relevance
“…The persistent inverse relationship between SES and mental health found in the literature (Hudson 1988(Hudson , 2005Perry 1996;Reynolds and Ross 1998;Warheit et al 1973) is confirmed to a great extent by our findings. Reynolds and Ross (1998), in particular, found that years of education have a significant effect on psychological well-being which lies beyond the access it provides to privileged positions in the economy and higher income.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The persistent inverse relationship between SES and mental health found in the literature (Hudson 1988(Hudson , 2005Perry 1996;Reynolds and Ross 1998;Warheit et al 1973) is confirmed to a great extent by our findings. Reynolds and Ross (1998), in particular, found that years of education have a significant effect on psychological well-being which lies beyond the access it provides to privileged positions in the economy and higher income.…”
Section: Discussionsupporting
confidence: 80%
“…Another persistent finding is a strong inverse relationship between depression and various indicators of socioeconomic status (SES) such as education, social class, income, type of housing and crowding (Hudson 2005;Murphy 1982;Reynolds and Ross 1998;Warheit et al 1973). Reviewing research carried out in the 1980s, Hudson (1988) reported that this relationship held regardless of the indicator used or the specific mental illness examined.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only 49.5% of the world's population are Internet users (Internet World Stats, 2016) and inequalities exist in the utilization of information and communication technologies (Mendonça, Crespo, & Simões, 2015). Indeed, individuals with low socioeconomic status are more likely to experience psychological problems (Hudson, 2005), but less likely to have access to the Internet (Pew Research Center, 2012). Consequently, the reach of eHealth treatments is confined by the digital divide.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to representations of mental health challenges, the novels appear to accurately represent the fact that in the United States today, those who struggle with mental illness are more likely to also struggle financially Numerous studies have found a correlation between mental health and poverty (Bassuk, Buckner, Perloff, & Bassuk, 1998;Belle & Doucet, 2003;Bogard, Trillo, Schwartz, & Gerstel, 2001;Brown & Moran, 1997;Bruce, Takeuchi, & Leaf, 1991;Gyamfi, Brooks-Gunn, & Jackson, 2001;Hudson, 2005). However, the novels may perpetrate or perpetuate gender stereotypes of which students and teachers need to be cognizant.…”
Section: From Bootstraps To Hands-up: a Content Analysis Of The Depicmentioning
confidence: 99%